EXAMINING STUDENTS’ AWARENESS AND BEHAVIOR IN DEALING WITH VIRTUAL LEARNING ENVIRONMENT - Najahah Najahah; Erna Nurkholida; Ulin Ni’mah Rodliya Ulfah (LP2M UIN KH.Achmad Siddiq Jember, 2022)
This research entitled “Examining Students’ Awareness and Behavior in Dealing with Virtual Learning Environment” intended to investigate the students’ awareness and behavior in dealing with the virtual learning environment. This research answered two questions; what is the students’ awareness of the virtual learning environment, and what is the students’ behavior in dealing with the virtual learning environment. This is survey research. The data was collected through a set of questionnaires spread through Google form using the link through the WhatsApp group. One hundred eighty-six students participated as respondents. The data of the responses were presented in bar and pie diagrams and explained descriptively to comprehensively reveal the students' awareness and behavior. The result said that related to the language and instruction of the lecturer in online learning; it seems that most students do not understand. More than half (58%) of the respondents neither agree nor disagree. Yet, 62% of the respondents agree that sharing applications (Google Classroom/WhatsApp Group), Virtual online learning (Zoom/Skype/Google meet), and Streaming audio (pre- recorder lecture) are valuable tools for learning online classes. Then about the online platform used in virtual learning, 49.5% agreed that Google Classroom or WhatsApp Group are more chosen than Zoom/Skype/Google meet. For all categories, the highest response is about internet connection. Most of the students agreed that internet connection is a problem. It reached 63.8%. About accessing the material, the highest response said that they had time to access the material and knew how to access it. While about the students’ behavior, many agreed that virtual/online learning can improcouldtheir confidence and self-discipline. But here, the percentage is not more than fifty. It is only 42.7% and 42.2%. Then, 45.9% of them neither agreed nor disagreed about online learning being more enjoyable, followed by disagreement in 27%. In the statement about easiness in interactions with classmates and lecturers, the highest percentage is disputed; it reached 38.9% and was followed by neither agree nor disagree. It means having interaction with lecturers and friends online is not as easy as in offline meetings.